2020
DOI: 10.3389/fped.2020.00010
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Transmission in a Primary School and a Private Language School. An Estimation of Infectivity

Abstract: Conclusion: This exposure investigation of two teachers detects high transmission among family contacts and school casual contacts. Recommendations for chemoprophylactic treatment in children <5 years showed low compliance, reflecting the difficulty of communication to staff, parents, and children in a school outbreak. It is essential to develop a new approach for this vulnerable group of patients. This approach could be improved, applied, and evaluated by National TB Control Programs, involving public and pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…Our results also demonstrated that excessive use of digital screens, especially with the device closer to the eye, is more likely to induce myopic development. The World Health Organization (WHO) offers a guideline to limit sedentary screen time for kids under 5 years old ( 33 ). Hence, parents should ask their kids to keep a safe distance while reading in online classes or to adopt alternative products like TV or projectors with relatively longer reading distance.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also demonstrated that excessive use of digital screens, especially with the device closer to the eye, is more likely to induce myopic development. The World Health Organization (WHO) offers a guideline to limit sedentary screen time for kids under 5 years old ( 33 ). Hence, parents should ask their kids to keep a safe distance while reading in online classes or to adopt alternative products like TV or projectors with relatively longer reading distance.…”
Section: Discussionmentioning
confidence: 99%
“…French national guidelines and others, such as the NICE guidelines from the United Kingdom, recommend systematic antibioprophylactic treatment for 0-2-year-old children regardless of the type of contact with an index case (7)(8)(9). Adherence to anti-TB chemoprophylaxis might be poor, and treatment might be associated with side effects (23)(24)(25)(26). In our study, of the 32 children younger than 2 years who had intermediate-or low-risk contact, 26 (81%) did not receive prophylactic treatment, and none developed TB.…”
Section: Discussionmentioning
confidence: 65%
“…Kedekatan kontak meningkatkan risiko infeksi. (Debulpaep et al, 2020). Investigasi kontak rumah tangga dari kasus indeks yang sama menghasilkan 40 kontak; 24 (60%) diskrining positif untuk gejala (Ustero et al, 2017).…”
Section: )unclassified